The Vent and Seep Biota Aspects from Microbes to Ecosystems - Kiel, Steffen (Topics in Geobiology ;, 2010)
Oases of life around black smokers and hydrocarbon seeps in the deep-sea were among the most surprising scientific discoveries of the past three decades. These ecosystems are dominated by animals having symbiotic relationships with chemoautotrophic bacteria. Their study developed into an international, interdisciplinary venture where scientists develop new technologies to work in some of the most extreme places on Earth. This book highlights discoveries, developments, and advances made during the past 10 years, including remarkable cases of host-symbiont coevolution, worms living on frozen methane, and a fossil record providing insights into the dynamic history of these ecosystems since the Paleozoic.